Karakteristik Fruit Leather Puree Jeruk Siam Kintamani (Citrus nobilis L.) dengan Perbandingan Bahan Pengikat Puree Rumput Laut (Eucheuma cottonii L.) Dan Biji Selasih (Ocimum basilicum L.) - Ni Komang Legaliang Aribaten; Gusti Ayu Kadek Diah Puspawati; I Nengah Kencana Putra (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Fruit leather is a sheet-shaped food product with a slightly tough texture, easy to roll, attractive color, and made from dried fruit puree. Kintamani Siamese orange can be processed into fruit leather, but its elasticity is lacking, so that the addition of a binder is required. The use of a combination of natural and synthetic binders in fruit leather has been widely studied, but combining natural binders is still rarely explored. Seaweed as a natural binder needs to be combined with other natural binders, such as basil seeds, to improve elasticity. This study aimed to determine the effect of the ratio of seaweed puree to basil seeds on the characteristics of fruit leather and to find the best ratio to produce Kintamani Siamese orange fruit leather with optimal characteristics. A Completely Randomized Design was used with six ratios of seaweed to basil seeds: 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80%, and 0%:100%, each with three replications. Data were analyzed using ANOVA at a 95% confidence level, followed by Duncan's multiple range test if significant effects were found. The results showed that the seaweed-basil seed ratio significantly affected (p<0,05) moisture content, tensile strength, elongation, elasticity, and hedonic values (appearance, overall acceptance). The best treatment was 60% seaweed and 40% basil seeds, with 12.13% moisture, 0.11 MPa tensile strength, 17.75% elongation, 0.64% elasticity, 41.55% total sugar, 4.06% crude fiber, slightly preferred texture and taste, and preferred appearance, aroma, and overall acceptance.